Post-Operative Haemorrhage: Conventional Tonsillectomy by Scalpel/Snare Versus Tonsillectomy by Applying Knot at Lower Pole Pedicle - Muhammad Aslam; Ashar Alamgir (Journal of Rawalpindi Medical College, 2012)
Background: To evaluate whether applying a knot at lower pole during tonsillectomy reduces post-operative haemorrhage. Methods: In this descriptive study 200 patients who were diagnosed cases of recurrent acute tonsillitis were enrolled. They were divided in two groups, each of 100 patients. In one group tonsillectomy was done by conventional scalpel/snare method. In second group tonsillectomy was done by applying knot at lower pole. Results: Recurrent acute tonsillitis was most common indication for tonsillectomy (n=185, 92%). Lower pole was most common site for post tonsillectomy haemorrhage (n=15, 8%). There was reduced incidence of post-operative haemorrhage in second group(6%) versus 32% in first group. Conclusion: Post-operative haemorrhage is significantly low if a knot is applied at lower pole pedicle, during tonsillectomy.